2015
DOI: 10.1097/mpg.0000000000000889
|View full text |Cite
|
Sign up to set email alerts
|

Infants Fed a Lower Calorie Formula With 2FL Show Growth and 2FL Uptake Like Breast‐Fed Infants

Abstract: Objectives:The aim of the present study was to examine the growth and tolerance of infants fed infant formulas with a caloric density closer to human milk (HM) supplemented with human milk oligosaccharides (HMOs) and to study uptake of the HMOs.Methods:A prospective, randomized, controlled, growth and tolerance study was conducted in healthy, singleton infants (birth weight ≥2490 g), who were enrolled by day of life (DOL) 5. Formula-fed infants were randomized to 1 of 3 formulas with a caloric density of 64.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
199
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(222 citation statements)
references
References 46 publications
5
199
1
11
Order By: Relevance
“…Prior incubation with LNnT also prevented adherence of S. pneumonia to chinchilla lungs (38). In addition to this, HMOs may play a systemic immunomodulatory role via direct mediation of cell-cell interactions in the immune system (41) when HMOs are absorbed intact into the circulation (26,28,42), and modulation of gut microbiota with indirect downstream effects on the immune system when largely indigestible HMOs reach the infant's colon (43). Duska-McEwen et al (40) recently reported that 2′FL and LNnT may decrease viral load in an in vitro model by enhancing innate immune responses to respiratory syncytial virus NM232 and influenza A virus H1N1 (NC99), 2 viruses associated with lower respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…Prior incubation with LNnT also prevented adherence of S. pneumonia to chinchilla lungs (38). In addition to this, HMOs may play a systemic immunomodulatory role via direct mediation of cell-cell interactions in the immune system (41) when HMOs are absorbed intact into the circulation (26,28,42), and modulation of gut microbiota with indirect downstream effects on the immune system when largely indigestible HMOs reach the infant's colon (43). Duska-McEwen et al (40) recently reported that 2′FL and LNnT may decrease viral load in an in vitro model by enhancing innate immune responses to respiratory syncytial virus NM232 and influenza A virus H1N1 (NC99), 2 viruses associated with lower respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, a chemically synthesized compound, 2ʹ fucosyllactose (2ʹFL), equivalent to the natur ally occurring 2ʹFL in HMO, was added to formula milk along with GOS. Although safe for infants, the 2ʹFL treatment provided no net dif ference in weight, length, head circumference and other measures compared with human milk over a 4 month period 44 . In another study by the same group, infants fed formula with 2ʹFL plus GOS had immune responses simi lar to breast fed infants in that both groups had lower levels of inflammatory cytokines than infants fed formula plus GOS 45 .…”
Section: Box 2 | Justification For the New Definition Of Prebioticsmentioning
confidence: 96%
“…Los HMOs aumentarían la eficiencia con que el organismo utiliza algunos nutrientes, efecto que fue investigado en un estudio acerca de los efectos de la 2'FL sobre el crecimiento de 424 lactantes quienes fueron alimentados con una fórmula experimental cuyo aporte de energía era similar al de la leche materna y las fórmulas infantiles 9 . Esta fórmula aportaba ~64,3 kcal/dL pero con un aporte de macronutrientes 5% menor.…”
Section: Ensayos Clínicos Con Hmos (Con éNfasis En Los Lactantes)unclassified
“…En la visita del día 28 o del día 42 las madres entregaron una muestra de leche; en los días 42 y 119 fueron obtenidas muestras de sangre, orina y deposiciones de los lactantes. No se observaron diferencias significativas para los parámetros antropométricos al comparar los distintos grupos entre sí en cuanto a su peso, largo corporal y perímetro cefálico 9 . El grupo alimentado con leche materna aumentó su peso más rápidamente entre los días 14 a 28 pero desde el día 84 y hasta el día 119 la ganancia de peso fue más rápida en el grupo EF2.…”
Section: Ensayos Clínicos Con Hmos (Con éNfasis En Los Lactantes)unclassified